This is what's in my book:

Let $\Delta$ be a polynomial given by: $\Delta = \prod_{1 \leq i \leq j \leq n} (x_i - x_j)$

For example, when $n=4$:

$\Delta = (x_1 - x_2)(x_1 - x_3)(x_1 - x_4)(x_2 - x_3)(x_2 - x_4)(x_3-x_4)$

For each $\sigma \in S_n$ let $\sigma$ act on $\Delta$ by permuting the variables in the same way it permutes their indices:

$\sigma(\Delta)=\prod_{1 \leq i \leq j \leq n} (x_{\sigma(i)} - x_{\sigma(j)})$.

And then we have the following example for $n=4$ and $\sigma = (1 2 3 4)$:

$\sigma(\Delta)=(x_2 - x_3)(x_2 - x_4)(x_2-x_1)(x_3-x_4)(x_3-x_1)(x_4-x_1)$

What I don't understand is how they get this result. I don't understand how $\sigma$ acts on $\Delta$. I can see that some terms are flipped (for example ($x_2-x_1$)) and that the order has changed, but why? Could somebody help me out?


We have $\sigma(1) = 2$ and $\sigma(2) = 3$, so the first factor $(x_1-x_2)$ becomes $(x_{\sigma(1)}-x_{\sigma(2)}) = (x_2 - x_3)$. Similarly for the rest. Does that clear things up?

  • $\begingroup$ Thanks, you're a hero! It's so obvious. $\endgroup$ – Nikki May 17 '16 at 15:25

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.